Father–daughter relationships and autonomy development during college. Issue 4 (1st August 2021) - Fletcher, Anne C.; Hohl, Marilyn L.; Lee, Grace Y.; McCurdy, Amy; Benito‐Gomez, Marta
Abstract: Female college students ( N = 26) from ethnically and socioeconomically diverse backgrounds participated in in‐depth qualitative interviews focused on the nature of their relationships with fathers. Holistic coding of interviews indicated three types of father–daughter relationships: connected, conflictual, and uncomfortable. Daughters perceived relationships with fathers as shaped by distinct factors all of which were, for the most part, in place prior to the transition to college. These included fathers' personality characteristics, parental marital disruptions, fathers' employment status or conditions, and shared interests and activities. Daughters also discussed ways in which college enrollment had impacted their own autonomy development and how their fathers' reactions to their increasing autonomy had changed the trajectories of their relationships—for better or for worse.